Study on the distribution characteristics of "Characteristic Ring" in irregular cross-section ventilation roadway. Issue 4 (July 2020) - Ding, Cui
Abstract: In order to study the airflow distribution in irregular cross-section roadway, the numerical simulation method were carried out to simulate the influence of hemispheres with radius of 100mm, 200mm, 300mm, and 400mm placed in different positions in the roadway on the distribution of "characteristic rings". The results showed that concave body is not the key factor influencing the distribution of "characteristic ring" in ventilation roadway. Convex body is the key factor influencing the distribution of "characteristic ring", the greater the ventilation velocity, the smaller the velocity gradient in the stable zone and the velocities in the stable area are more closely to the average velocity. As the increase of ventilation velocity, the velocity gradient is larger in transition zone. The size and position of the convex and concave bodies are not the key factors influencing the velocity distribution on the central axis of cross-section.